Diversity and Transformation within Varieties of Capitalism, Work, and Employment: The Sustainability of Alternatives to Neo-Liberalism - Wood, Geoffrey (Labour / Le Travail, 2008)
The article reviews and comments on several books including "Changing Governance of Local Economies," edited by Colin Crouch, Patrick Le Galès, Carlo Trigilia, and Helmut Voelzkow, "Convergence and Persistence in Corporate Governance," by Jeffrey N. Gordon and Mark J. Roe, and "The Global and the Local: Understanding the Dialectics of Business Systems," by Arndt Sorge.
Keywords: BOOKS -- Reviews; CHANGING Governance of Local Economies (Book); CONVERGENCE & Persistence in Corporate Governance (Book); CROUCH, Colin; GLOBAL & the Local: Understanding the Dialectics of Business Systems, The (Book); GORDON, Jeffrey N.; LE Gales, Patrick; Nonfiction; ROE, Mark J.; SORGE, Arndt; TRIGILIA, Carlo; VOELZKOW, Helmut